Exploring Pharmacy Students’ Techniques in Translating Pharmaceutical Texts from English into Bahasa Indonesia - Kailani, Ahmad; Rafidiyah, Dina (JEES (Journal of English Educators Society), 2020)
Translating an L1 (source text) into a target language would be a daunting task and time-consuming work for students who are non-native speakers. It might be more challenging when the L1 text is a discipline specific text. Many words and specific terms are difficult to translate, and often unintended meanings emerge during this translation process. Although there has been considerable research on the translation studies, there has been still little study on how translators cope with the challenges. To fill this void, this case study is aimed to describe techniques employed by students majoring pharmacy in translating direction for use texts from English into Bahasa Indonesia. Adopting Vinay’s and Darbelnet’s (1996) translation methodology, this research is aimed to describe the translation process that students already undertook in order to produce texts that appropriately work in a particular social context. There are four drug brochures taken as samples of analysis. These texts are students’ assignment for the topic of translation. This is a group work and part of the whole assessment. The study provides detailed and specific examples of how students tackle the challenges of translating discipline specific texts into equivalent languages that are socio-culturally and linguistically acceptable. HIGHLIGHTS: Translating a text is not simply to transfer the meaning of source text into the target text, but it requires the translator to have sufficient discipline specific knowledge. The challenges and problems faced by translators would be different from one another since each discipline specific text requires different strategies.